ENVIRONMENTAL IMPACTS CAUSED BY RESIDUAL VEGETABLE OIL IN THE SOIL-PLANT SYSTEM - Thode Filho, Sérgio; Paiva, Julieta Laudelina de; Franco, Heider Alves; Perez, Daniel Vidal; Marques, Monica Regina da Costa (Ciência e Natura, 2017)
Vegetable oils are widely used for food production at different levels: domestic, commercial or industrial. The estimated production of vegetable oil, in Brazil, is three billion liters per year. Only 2.5% of cooking oil waste (WCO) are recycled. The environmental impacts caused by WCO arrangement in soils still need to be better studied. The interaction of soils and organic pollutants makes it difficult to evaluate its behavior in the environment. This paper presents to evaluate the environmental impact of OVR in two Brazilian soils (sandy and loamy) and to estimate the terrestrial toxicity level (leakage test) and phytotoxicity (germination tests using lettuce seeds - Lactuca sativa L. – as well as in lettuce cultivation under greenhouse conditions). After leaching, the sandy soil had a slight lower WCO adsorption capacity than the clayey soil. The introduction of WCO caused clayey soil compaction. The WCO presence was toxic to earthworms, regardless of soil type. WCO negatively influenced germination and radicle growth in the eco toxicity assays. The different tested doses of WCO in lettuce (Lactuca sativa L.) cultivation caused changes in plant morphology for all physical parameters analyzed for both soils. We concluded that the WCO is a potential contaminant residue when improperly disposed over the soil, compromising the soil-plant system.